Окремі аспекти “концепції відновлення архітектурного образу і функції резиденції в с. Підгірці” - Ремешило-Рибчинська, О. І.; Remeshylo-Rybchyns’ka, O. I. (Видавництво Національного університету “Львівська політехніка”, 2005)
Проаналізовано стан архітектурних пам’яток підгорецького палацово-паркового комплексу, розглянуто Програму робіт з інвентаризації об’єктів. Зазначено специфічні особливості окремих шляхів з реалізації Програми, вказано на необхідність комплексного підходу до формування концепції відновлення просторового наповнення історичного ландшафту Вороняцького горбогірного пасма.

The article analyzes the condition of architectural monuments of the palace and park complex in Pidhirtsi village. It provides the information about the existing “Program on taking stock of the architectural monuments”, emphasizes some specific ways to implement the program, indicates the need of applying the complex approach to the development of the concept of renovating the special filling of the historical landscape of Voroniats’ki mountain spine.
The implementation specificity of the “Program on taking stock of the architectural monuments” in Pidhirtsi village
Keywords: програма; концепція; інвентаризація; пам’ятка; . 711